On-line quizzes to evaluate comprehension and integration skills - José David Badia Valiente; Françoise Olmo Cazevieille; José Manuel Navarro Jover (OmniaScience, 2016)
This work demonstrates the use of a 2.0 tool, namely, Socrative, to evaluate one of the cross-curricular competences indicated by the Universitat Politècnica de València, specifically, comprehension and integration. It has been applied to the courses in different areas: sciences, engineering and languages. As part of its implementation, activities were proposed that could be done at the beginning, during or at the end of the class to, on the one hand, help students acquire the knowledge associated with the course(s), and on the other, gather evidence that demonstrates acquisition of said competence. The results show a high level of satisfaction by the students with the use of the Socrative tool as an element to promote active participation and the acquisition of the cross-curricular competence of comprehension and integration; therefore, its extension to other courses has been suggested.